2017
DOI: 10.1002/esp.4194
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing extreme post‐wildfire floods: a comparison of convective and mesoscale events

Abstract: In much of western United States destructive floods after wildfire are frequently caused by localized, short‐duration convective thunderstorms; however, little is known about post‐fire flooding from longer‐duration, low‐intensity mesoscale storms. In this study we estimate and compare peak flows from convective and mesoscale floods following the 2012 High Park Fire in the ungaged 15.5 km2 Skin Gulch basin in the northcentral Colorado Front Range. The convective storm on 6 July 2012 came just days after the wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 82 publications
(137 reference statements)
3
55
1
Order By: Relevance
“…Bales et al, 2006;Stratton et al, 2009), and given that this particular basin failed and adjacent similar basins did not, one possibility is this basin received higher rainfall. Brogan et al (2017) report an environment where mesoscale precipitation resulted in greater geomorphic change than convective precipitation via fluvial processes. However, Benavides-Solorio and Macdonald (2005) found that convective storms produce >90% of hillslope plot erosion, and Kampf et al (2016) found average sediment yields doubled in convective versus mesoscale storms.…”
Section: Precipitation Characterization and Context For Debris-flow Pmentioning
confidence: 99%
“…Bales et al, 2006;Stratton et al, 2009), and given that this particular basin failed and adjacent similar basins did not, one possibility is this basin received higher rainfall. Brogan et al (2017) report an environment where mesoscale precipitation resulted in greater geomorphic change than convective precipitation via fluvial processes. However, Benavides-Solorio and Macdonald (2005) found that convective storms produce >90% of hillslope plot erosion, and Kampf et al (2016) found average sediment yields doubled in convective versus mesoscale storms.…”
Section: Precipitation Characterization and Context For Debris-flow Pmentioning
confidence: 99%
“…After the fire streamflow noticeably increased and became perennial. One week after the fire had been contained a convective storm in SG generated large amounts of hillslope and upstream channel erosion, an estimated peak flow of nearly 30 m 3 s -1 km -2 , and extensive downstream deposition (Brogan et al, 2017); this event is referred to as the 'convective flood' 15 throughout the paper. No comparable storm occurred in HG, but in September 2013 a large mesoscale storm caused widespread and prolonged high flows in both watersheds.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Brogan et al (2017) examine channel changes through time in response to convective and longer-duration, lower intensity mesoscale rainfall. Closely related to these issues are concerns about how changing climate and increasing occurrence of wildfires might force river ecosystems across a threshold of process or morphology.…”
Section: Papers In the Themed Issuementioning
confidence: 99%
“…Closely related to these issues are concerns about how changing climate and increasing occurrence of wildfires might force river ecosystems across a threshold of process or morphology. Brogan et al (2017) examine channel changes through time in response to convective and longer-duration, lower intensity mesoscale rainfall. Working in the same, well-studied Colorado field site with the 2012 fire (see Wagner et al, 2015, Sosa-Pérez and MacDonald, 2017, and Wohl and Scott, 2017, Brogan et al document channel responses in the 15.5 km 2 Skin Gulch drainage.…”
Section: Papers In the Themed Issuementioning
confidence: 99%
See 1 more Smart Citation